Spontaneous Bladder Perforation in an Infant Neurogenic Bladder: Laparoscopic Management - Daniel Cabezalí Barbancho; Felix Guerrero Ramos; Francisco López Vázquez; Adolfo Aransay Bramtot; Andrés Gómez Fraile (Case Reports in Urology)
Spontaneous bladder perforation is an uncommon event in childhood. It is usually associated with bladder augmentation. We are presenting a case of bladder rupture in an infant with neurogenic bladder without prior bladder surgery. Three days after lipomyelomeningocele excision the patient showed signs and symptoms of acute abdomen. The ultrasound exploration revealed significant amount of intraperitoneal free fluid and therefore a laparoscopic exploration was performed. A posterior bladder rupture was diagnosed and repaired laparoscopically. Currently, being 3 years old, she keeps successfully dry with clean intermittent catheterization. Neurogenic bladder voiding function can change at any time of its evolution and lead to complications. Early diagnosis of spontaneous bladder rupture is of paramount importance, so it is essential to think about it in the differential diagnosis of acute abdomen.